The effect of first step right atrial mapping (FRAM) on ablation duration and fluoroscopy exposure during cavotricuspid isthmus ablation of atrial flutter - Guan, Fu; Saguner, Ardan M.; Breitenstein, Alexander; Wang, Mia; Molitor, Nadine; Brunckhorst, Corinna; Wolber, Thomas; Duru, Firat (Frontiers in Cardiovascular Medicine, 2023)
Aim To investigate the clinical significance of right atrial mapping prior to cavotricuspid isthmus (CTI) ablation in patients with typical atrial flutter (AFL). Methods Clinical and ablation parameters were retrospectively assessed and compared in patients undergoing CTI ablation with or without a first-step right atrial mapping (FRAM) by using the CARTO 3D mapping system. Results CTI block by radiofrequency ablation (RFA) was achieved in all 143 patients. In the FRAM group there was a shorter ablation duration and fluoroscopy exposure compared with the non-FRAM group. CHA2DS2-VASc score was associated with higher ablation durations, more ablation applications and increased fluoroscopy exposure. Body mass index (BMI) was associated with longer ablation duration and more ablation applications. Furthermore, patients with reduced left ventricular ejection fraction (LVEF) had longer ablation durations and more fluoroscopy exposure. One patient in the non-FRAM group developed cardiac effusion after ablation. None of the patients had recurrence after 6 months of follow-up. Conclusions Patients with high BMI, high CHA2DS2-VASc score and reduced LVEF may benefit from the FRAM approach by reducing ablation duration, number of ablation applications and fluoroscopy exposure.